Kepemimpinan kepala sekolah dalam meningkatkan kualitas sekolah unggul SMA Negeri 1 Gemolong - Husen Rofiqul A'la; Nurul Latifatul Inayati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Education in school is one of the most important stages in life. With school, a person is able to lift the stupidity that is in him. With education, a person will hold one of the keys to success. Education at that school will also realize the noble ideals of this nation in accordance with the mandate of the 1945 Constitution. There is one important element in schools, namely the school principal. Without the principal, there is no leader and manager in the school institution. There are several types of school principal leadership that determine the direction to be achieved from an educational institution. In this study, the author will discuss the leadership role of the principal of SMA N 1 Gemolong, along with its innovations and advantages (swot). This research uses field research and direct face-to-face interviews with informants. The data collection technique in this paper is to make observations at SMA N 1 Gemolong. interview with the principal of SMAN 1 Gemolong, Drs. Suparno, M.Eng. face-to-face. The principal of SMA Negeri 1 Gemolong has a leadership style/model of active participation from all stakeholders in the school. The innovations carried out focus on developing human resources at SMA N 1 Gemolong in an effort to develop school quality.